The Effect of Deep Breath Relaxation Techniques on The Risk of Violent Behavior in Patients with Mental Disorders at Soerojo Hospital - Intan Puspa Wijaya; Ita Apriliyani (LPPM Universitas Harapan Bangsa, 2024)
Background: The increasing cases of mental disorders in Indonesia need special attention in the application of nursing practice, the need for simple effective interventions to control violent behavior is important to do in hospitals. Objective: This study aims to examine the effect of deep breathing techniques in managing the risk of violent behavior in patients with mental disorders. Research method: Descriptive case study method with sampling technique used is purposive sampling, the number of samples is 1 person in Lily Room 3 Soeroyo hospital, the research process includes assessment, nursing diagnosis, planning, implementation, and nursing evaluation. Research results: The use of breath relaxation techniques for 3 days reduced the score of aggressive behavior, speaking harshly, loud voices from 1 (increased) to 5 (decreased). Conclusion: this study shows a decrease in violent behavior and increased patient self-control along with the application of nursing interventions.